Combination of Areca catechu , Sauropus androgynous , and Mineral Block is Effective to control Nematode in Goats - Henni Vanda; Muhammad Hambal; Farida Athailah; Mustafa Sabri (The International Journal of Tropical Veterinary and Biomedical Research, 2017)
A study has been conducted to investigate the effect of two local herbs in Indonesia; Areca catechu nut and Sauropus androgynous leaf, combined with mineral block to treat gastro intestinal nematode in goats. A.catechu is well known to have anthelmintic property due to its alkaloid and tannin content, and S.androgynus also contains tannin, alkaloid and steroid that will enhance the anthelmintic property of those herbals.  As many as 80 goats had been divided into 4 groups; 20 were treated with albendazole (Group A), 20 were given A.catechu and S.androgynus (Group B), 20 were given combination of A.catechu, S.androgynus, and mineral block (Group C), and 20 as negative control (Group D). The result revealed that herbal treatment showed significantly effective toward nematodes in gastro intestinal, demonstrated by declining egg worm of Group B and C. Body weight improvement and overall performance in Group C was higher compared to other groups. However, goats treated with albendazole showed slightly better results in the decreasing amount of egg worms found after treatment. Nevertheless, A.catechu and S.androgynus are potential anthelmintic herbal; combination with mineral block will enhance the anthelmintic activity. Therefore they are good options for treating helminthiasis in livestock.